Merging biotechnology with biological control: banana Musa tissue culture plants enhanced by endophytic fungi - Paparu, P.; Dubois, T.; Athman, S.; Kapindu, S.; Coyne, D.; Gold, C.; Adipala, E.; Mukwaba, E. (2004)
Among the major constriats to highland cooking banana (Musa spp. AAA-EA) production in Uganda is the high pests infestation levels. Most important are the banana weevil cosmopolites sordidus and a complex of plant parasitic root nematodes of which Radopholus similis is the most important. Clean planting material, such as tissue culture derived plants, is now being promoted in Uganda for establishments for new fields, although pest re-infestation remains a vital concern. Fungal endophytes are microorganisms that colonize plant tissue internally for at least part of their life cycle tp form mutualistic relationships with their host plants, including antagonism to pest and diseases.